The Development of Capabilities of Young People with Low Skills. The Case Study of a Vocational Education Programme in Poland. - Karolina Sztandar-Sztanderska; Marianna Zieleńska (Social Work & Society, 2012)
The article presents results of a case study of educational programme, which was designed to answer the structural problems of vocational schooling in Poland. It aimed at improving skills of students from vocational schools and was provided by a big employer operating in the sector of power industry. The analysis of empirical material consisting of interviews, documents, legal regulations and statistics, focused on identifying factors working in favour of building capabilities of its participants (increasing spectrum of their possible life choices). This particular case study gives insight into more general mechanisms contributing to the development of freedom of youth with low skills or impeding it by reproduction of inequalities.